A matemática nos anos finais do Ensino Fundamental: um estudo visando conhecer as principais dificuldades de ensino e aprendizagem em Cachoeira do Sul (RS) - Amador, Ivonete Pereira (2017)
This dissertation is about a master‟s degree research that had the objective to find in the daily classroom possible way-outs to the difficulties faced in the teaching and learning process of Mathematics in the final years of the middle school, considering the rural and urban municipal schools in Cachoeira do Sul/RS. This was an empirical research that had as subjects 20 teachers and 75 students, at a total of 10 schools in the mentioned city. For the data collect realization it was applied semi-structured questionnaires, with 30 questions for teachers and 26 for students. These questionnaires had the intention to register the perception regarding the motivation, learning, difficulties, pedagogical actions and relevant aspects of their formation. The data collect‟s analysis and interpretation were performed through the use of categories of Bardin‟s studies (2016). For the interpretation of the questionnaires, it was stablished three groups: initial, intermediary and final categories. After gathering the categories, it was chosen to make an analysis movement of the final category, which includes the intermediary category. These are defined trough the initial categories with the pretension to return to the original texts to a better understanding and this way, expressing a look over the meanings and senses realized in the questionnaires. For that, the critical theoretical studies of Saviani, Libâneo and Skovsmose were used as contributions. Among the findings with the analysis made, it stands out that everyone showed compromise with the teaching and learning process. It is pointed out that these same teachers highlighted that: it is up to the teacher to search for teaching methods that can facilitate the learning absorption and motivates the student to learn and to use creativity to resolve problems that involve his reality and the society reality as an all. It was also verified the importance of an affectivity relation between teachers and students. Another understood factor, and which influences significantly at the discipline learning, is related to the impressions that students have about learning techniques used by teachers. We conclude that, exclusively, through knowledge we can instigate the student to be participatory, conscious of his rights and duties, emancipating his creativity, believing in himself, recognizing himself as an apprentice, having wisdom and self-criticism.